Association of Serious Fall Injuries among United States End Stage Kidney Disease Patients with Access to Kidney Transplantation - Plantinga, Laura C. (Clin J Am Soc Nephrol, 2018)
BACKGROUND AND OBJECTIVES: Serious fall injuries in the setting of ESKD may be associated with poor access to kidney transplant. We explored the burden of serious fall injuries among patients on dialysis and patients on the deceased donor waitlist and the associations of these fall injuries with waitlisting and transplantation. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Our analytic cohorts for the outcomes of (1) waitlisting and (2) transplantation included United States adults ages 18–80 years old who (1) initiated dialysis (n=183,047) and (2) were waitlisted for the first time (n=37,752) in 2010–2013. Serious fall injuries were determined by diagnostic codes for falls plus injury (fracture, joint dislocation, or head trauma) in inpatient and emergency department claims; the first serious fall injury after cohort entry was included as a time-varying exposure. Follow-up ended at the specified outcome, death, or the last date of follow-up (September 30, 2014). We used multivariable Cox proportional hazards models to determine the independent associations between serious fall injury and waitlisting or transplantation. RESULTS: Overall, 2-year cumulative incidence of serious fall injury was 6% among patients on incident dialysis; with adjustment, patients who had serious fall injuries were 61% less likely to be waitlisted than patients who did not (hazard ratio, 0.39; 95% confidence interval, 0.35 to 0.44). Among incident waitlisted patients (4% 2-year cumulative incidence), those with serious fall injuries were 29% less likely than their counterparts to be subsequently transplanted (hazard ratio, 0.71; 95% confidence interval, 0.63 to 0.80). CONCLUSIONS: Serious fall injuries among United States patients on dialysis are associated with substantially lower likelihood of waitlisting for and receipt of a kidney transplant.